2023
DOI: 10.1007/s10096-023-04548-2
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal colonization with multidrug-resistant Enterobacterales: screening, epidemiology, clinical impact, and strategies to decolonize carriers

Abstract: The clinical impact of infections due to extended-spectrum β-lactamase (ESBL)- and/or carbapenemase-producing Enterobacterales (Ent) has reached dramatic levels worldwide. Infections due to these multidrug-resistant (MDR) pathogens—especially Escherichia coli and Klebsiella pneumoniae—may originate from a prior asymptomatic intestinal colonization that could also favor transmission to other subjects. It is therefore desirable that gut carriers are rapidly identified to try preventing both the occurrence of ser… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 277 publications
(387 reference statements)
2
31
0
Order By: Relevance
“…Virulence genes identified amongst the E. coli isolates are known to play a significant role in influencing the degree of pathogenicity of bacteria infection in confirmed disease patients in some reported cases (36,37). Although the K. quasivariicola and Enterobacter hormaechei harbored no virulence gene, the presence of more than three plasmid replicons associated with ARGs is a significant concern as reports of colonizing enteric bacteria resulting in infections are facilitated by MDR and plasmid carriage (38).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Virulence genes identified amongst the E. coli isolates are known to play a significant role in influencing the degree of pathogenicity of bacteria infection in confirmed disease patients in some reported cases (36,37). Although the K. quasivariicola and Enterobacter hormaechei harbored no virulence gene, the presence of more than three plasmid replicons associated with ARGs is a significant concern as reports of colonizing enteric bacteria resulting in infections are facilitated by MDR and plasmid carriage (38).…”
Section: Discussionmentioning
confidence: 99%
“…Resistance to these drugs, some of the most common antibiotics used in treating diarrhea diseases in children, could pose a challenge in future infections with these resistant strains. Also, reports have shown that most cases of infection with MDR enterics are not just from a person-to-person transmission or from contaminated water/food but could also be from the individual colonized by these MDR bacteria (38).…”
Section: Discussionmentioning
confidence: 99%
“…4B) with minimal pairwise SNP differences ( i.e., < 10 SNPs), suggesting the long duration of colonization achievable by 3GC-R Kp [69]. We envision that a strategy of targeted K. pneumoniae gastrointestinal tract decolonization, such as using CRISPR-based technologies, could be part of the future treatment of 3GC-R Kp infections [70].…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have estimated the risks of extraintestinal infections associated with gut carriage of multi-drug resistant E. coli. Generally, these studies have focused on the risks of bacteremia and included samples from hospital/ICUadmitted patients and/or those who underwent various organ transplant procedures [37][38][39][40]. The correlation between gut carriage and consequent drugresistant infections has been sufficiently strong to motivate studies on gut decolonization of patients at risk, employing methods such as fecal microbiome transplantation, probiotics, and/or phage therapies [37,[41][42][43][44].…”
Section: Introductionmentioning
confidence: 99%
“…Generally, these studies have focused on the risks of bacteremia and included samples from hospital/ICUadmitted patients and/or those who underwent various organ transplant procedures [37][38][39][40]. The correlation between gut carriage and consequent drugresistant infections has been sufficiently strong to motivate studies on gut decolonization of patients at risk, employing methods such as fecal microbiome transplantation, probiotics, and/or phage therapies [37,[41][42][43][44]. To our knowledge, however, there have been no observational prospective studies to assess the value of characterizing gut-colonizing bacteria for predicting the risks and guiding the antimicrobial treatment of such a vastly common antibiotictreated medical condition as UTI.…”
Section: Introductionmentioning
confidence: 99%